Discharge and stability studies for the new readout chambers of the upgraded ALICE TPC. (30th May 2017) - Deisting, A.; Garabatos, C.
Abstract: The ALICE (A Large Ion Collider Experiment) Time Projection Chamber (TPC) at CERN LHC is presently equipped with Multi Wire Proportional Chambers (MWPCs). A gating grid prevents ions produced during the gas amplification from moving into the drift volume. The maximum drift time of the electrons together with the closure time of the gating grid allows a maximum readout rate of about 3 kHz. After the Long Shutdown 2 (from 2021 onwards), the LHC will provide lead-lead collisions at an expected interaction rate of 50 kHz. To take data at this rate the TPC will be upgraded with new readout chambers, allowing for continuous read-out and preserving the energy and momentum resolution of the current MWPCs. Chambers with a stack of four Gas Electron Multipliers (GEMs) fulfil all the performance requirements, if the voltages applied to the GEMs are tuned properly. In order to ensure that these chambers are stable while being operated at the LHC, studies of the discharge behaviour were performed. We report on studies done with small prototypes equipped with one or two GEMs. Discharges were voluntarily induced by a combination of high-voltages across the GEM(s) and highly ionising particles. During these studies, the phenomenon of ``secondary discharges'' has been observed. These occur only after an initial discharge when the electric field above or below the GEM is high enough. The time between the initial and the secondary discharge ranges from several 10 μs to less than 1 μs, decreasing with increasing field. Using decoupling resistors in the high-voltage supply path of the bottom side of the GEM shifts the occurrence of these discharges to higher electric fields.